Magical Realism in "Sangha san Batesi" and "Betaal Pachesi" - DR. MUHAMMAD RAMZAN (دریافت, 2025)
The term "Magical realism" translated as “Jadowi Haqiqat” in Urdu is a modern technique. Hawan Ralpho, for the first time, used it in his stories. The Latin novelist Gabriel Garcia, by using the technique of "Magical Realism" in his novel “Hundred Years of Solitude” in 1967, revolutionized the style of narration all over the world, and Urdu Literature is no exception especially in the first half of twentieth century characterized by the use of various descriptive techniques like letters, diaries, flash backs, flash forwards, surrealism and realism etc. Magical Realism is one of such powerful techniques.” Sangha San Batesi” and “Bettal Pachesi” stories are related to the imaginary and ideal world. Where different characters including giants, fairies, jinns, ghosts, ascetics, jogis and leaves keep the reader in a wonderful struggle from the beginning to the end. All the stories of “Singhasan Batesi” and “Bettal Pachesi” evoke an atmosphere of imagination and romance. In addition to the religious and cultural landscape, there is also a conflict between them. Raja Bakarmajit's character is Dev Malay and a character with transcendent abilities. Raja Bakarmajit's tenure has been described in the words of government puppets. In these stories, the magic and talismanic atmosphere surrounds the characters of good and bad everywhere in a believable manner. Apart from this, there are glimpses of Bikramjit's courage, generosity, courage, wisdom and wise decisions. In the stories of “Singhasan Batesi” and “Bettal Pachpesi”, the situation of the supernatural and the supernatural elements creates a surprise for the reader.